2020
DOI: 10.1289/ehp7045
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Cardiopulmonary Evaluation of Rats Chronically Exposed to Traffic-Related Air Pollution

Abstract: Background: Traffic-related air pollution (TRAP) is made up of complex mixtures of particulate matter, gases and volatile compounds. However, the effects of TRAP on the cardiopulmonary system in most animal studies have been tested using acute exposure to singular pollutants. The cardiopulmonary effects and molecular mechanisms in animals that are chronically exposed to unmodified air pollution as a whole have yet to be studied. Additionally, sex-dependent toxicity of TRAP exposure has rarely been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 95 publications
2
28
0
Order By: Relevance
“…An important finding is that the mean maximum refractive intensity of the particles in the brains of TRAP animals was significantly greater than those in the brains of FA controls, suggesting differences in elemental composition. Although chemical analysis of these tissue-embedded particles was beyond the scope of this study, our previous characterization of TRAP collected from this facility showed that elemental, organic, and total carbon levels, as well as levels of copper, titanium, zinc, iron, sulfur, and silicon were significantly elevated in air from TRAP compared with FA exposure chambers ( Edwards et al. 2020 ; Patten et al.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…An important finding is that the mean maximum refractive intensity of the particles in the brains of TRAP animals was significantly greater than those in the brains of FA controls, suggesting differences in elemental composition. Although chemical analysis of these tissue-embedded particles was beyond the scope of this study, our previous characterization of TRAP collected from this facility showed that elemental, organic, and total carbon levels, as well as levels of copper, titanium, zinc, iron, sulfur, and silicon were significantly elevated in air from TRAP compared with FA exposure chambers ( Edwards et al. 2020 ; Patten et al.…”
Section: Discussionmentioning
confidence: 98%
“…The tunnel vivarium, which has been previously described ( Berg et al. 2020 ; Edwards et al. 2020 ; Patten et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent pilot study reported in Environmental Health Perspectives, investigators sought to address this issue using a real-world model of TRAP exposure in rats. 2 Worldwide, ambient air pollution is estimated to cause 3.8 million premature deaths per year due to cardiovascular and respiratory diseases. 3,4 Several studies have reported an association between acute exposure to highly concentrated PM and development of cardiopulmonary dysfunction in humans and animals.…”
mentioning
confidence: 99%